Effects of Influencer Marketing on Luxury Fashion and the Purchasing Behaviour of Generation Z - Marín Dueñas, Pedro Pablo; Gómez Carmona, Diego; Cano Tenorio, Rafael (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study aims to analyse how luxury fashion brands are adapting their digital communication to the new demands arising from generation Z, and more specifically, how they are implementing influencer marketing in their communication strategies and the effect this has on the behaviour of generation Z consumers. Based on methodological triangulation, a survey of a sample of consumers, interviews with luxury fashion industry experts and a content analysis applied to the publications of luxury fashion influencers and a selection of luxury brands have been implemented. The results provide a comprehensive view of the main challenges faced by companies in this sector, what strategies they are implementing, with special emphasis on influencer marketing, and what actions should be taken to connect with the Generation Z audience.